Pengaruh Integrated Reporting Terhadap Asimetri Informasi Dengan Kualitas Laba Sebagai Pemoderasi Pada Perusahaan Pemenang Asia Sustainibility Report Award (ASRA) - Fadila Kurniawati; Nurmala Ahmar; Dwi Prastowo Darminto (FEB Universitas Sultan Ageng Tirtayasa, 2020)
ABSTRACT The purpose of this study were examine and analyze the effect of the presentation of elements of integrated reporting toward information asymmetry with earning quality as a moderation in the winners company 2018 of Asian sustainability award (ASRA) with 36 observations for the period 2017-2018. The method of data analysis in this study was Stuctural Equation Modeling (SEM) with Partial Least Square (PLS) approach using the WarpPLS 5.0 program. The results of this study are elements of integrated reporting of organizational governance, business models and future prospects directly influence information asymmetry. While the integrated reporting elements of the organization's description and external environment, organizational governance, business models, strategy and allocation, performance, and the basis for disclosing the elements affect the information asymmetry with earnings quality as a moderating factor. Earnings quality as a moderating variable also directly influences information asymmetry. The contribution of this study adds a reference for further research.